2011
DOI: 10.1016/j.transproceed.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Cost–Benefit Estimation of Cadaveric Kidney Transplantation: The Case of a Developing Country

Abstract: These results demonstrated that kidney transplantation along with a better quality of life for patients are a cost-saving decision for developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 14 publications
4
20
0
1
Order By: Relevance
“…1, 2, 3, 4 This is especially the case for sub-Saharan Africa, where maintenance dialysis is beyond the reach of most of the population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, 2, 3, 4 This is especially the case for sub-Saharan Africa, where maintenance dialysis is beyond the reach of most of the population.…”
Section: Introductionmentioning
confidence: 99%
“…KT is recognized globally as the gold standard treatment modality for ESRD patients because of its overall cost effectiveness, guaranteeing of an almost normal quality of life, as it affects different domains and reduced frequency of hospital visits and hospitalizations. 1, 2, 3, 4, 13 It however has its constraints, which include the huge financial outlay at the outset, shortage of donor organs, challenges of immunosuppression and, very recently, organ trafficking 13, 21, 22, 23, 24, 25, 26, 27, 28 , This current review is aimed at assessing kidney transplant activities in Nigeria from the years 2000–2010 with the objective of highlighting the outcomes and challenges. This is to be able to proffer ethically and culturally acceptable solutions to the identified challenges without compromising standards.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that the expected present value of costs associated with dialysis is approximatelyUS$134,000, whereas the expected costs of a transplant amount to nearly US$106,000. Overall, the study concluded that cost savings associated with cadaveric kidney donation are positive and substantial, thus cadaveric kidney transplantation is highly encouraged as a primary strategy of renal replacement therapy [11].…”
Section: Comparative Cost-effectiveness Of Esrd Treatment Optionsmentioning
confidence: 98%
“…Señor Editor, El trasplante de órganos sólidos es una herramienta terapéutica consolidada, que entrega demostrados beneficios en supervivencia y costo-efectividad para los pacientes 1 , siendo en occidente los donantes cadavéricos en muerte cerebral la principal fuente de injertos 2 . Un fenómeno presente en todo el mundo es la brecha entre la necesidad de órganos y su real disponibilidad, incluso en aquellos sistemas de procuramiento más exitosos en la detección de donantes 2 .…”
Section: Organ Transplantation In Chileunclassified